Charge transfer of CsMnFe-Prussian blue analogue induced by pressure and temperature. (4th May 2022) - Zhang, Qinghang; Mo, Jiajun; Xie, Yimin; Xia, Yanfang; Liu, Min
ABSTRACT : The charge transfer properties of CsMnFe-PBA after 40 MPa pressure treatment and under temperature variation were investigated using temperature-variable Mössbauer spectrum. Both the 0 and 40 MPa treated samples have face-centered cubic structure, and the lattice constants are 10.504 Å and 10.499 Å. The room temperature Mössbauer spectra show that the sample at 0 MPa consists of HT and LT phases, and only HT phase is present at 40 MPa. Variable-temperature Mössbauer spectra revealed the thermal phase transition from 220 K to 130 K, which is accompanied by charge transfer from Fe III (LS, t2g 5 eg 0 )-CN-Mn II (HT) to Fe II (LS, t2g 6 eg 0 )-CN-Mn III (LT), and the phase transition temperature during warming and cooling are different. It is concluded that there is a thermally induced hysteresis loop induced by charge transfer in the CsMn[Fe(CN)6 ]· x H2 O, and the pressure and temperature induce the charge transfer in the compound.